Environmental sustainability initiatives adopted by logistics service providers in a developing country – an overview in the Brazilian context - Froio, Patrícia Jacomini [UNESP]; Bezerra, Barbara Stolte [UNESP] (Elsevier, 2021)
The aim of this research was to determine the main environmental sustainability initiatives practiced by some Brazilian Logistics Service Providers (LSP) and identify future projects and programs. Even though this topic has gained considerable attention from the international scientific community, most studies do not focus on LSP in emerging economies. Therefore, this exploratory study collected data from the largest LSP companies in Brazil using a semi-structured questionnaire. The software NVivo10 was used to conduct a content analysis with coding data from the questionnaires, as well as to search for patterns in the respondents’ answers. The findings point out that the surveyed companies have carried out several initiatives, such as energy efficiency, costumer recognition and CO2 emissions reduction. In addition, most of sustainable initiatives are intra-organizational, when compared to inter-organizational ones. The majority of surveyed LSPs had plans to implement sustainable programs involving more intra-organizational actions. However, actions towards customer collaboration were rarely mentioned. The main difficulties related to the implementation of sustainable initiatives are: high cost, compliance with legislation when required, difficulty in involving customers in sustainable projects and management of outlying branches due to extensive territory.
Keywords: Environmental initiatives; Green initiatives; Green logistics; Sustainable development; Third-party logistics